Surgical treatment for complete resection of transthoracic and abdominal schwannoma with diaphragm invasion using the transthoracic approach: a case report and literature review - Zhang, Wen-jun; Pang, Li-song; Hu, Dong-xia; Le, Yi-guan (Frontiers in Oncology, 2024)
BackgroundThe removal of schwannomas involving the chest and abdominal cavities is difficult, which requires a high level of overall proficiency and technical expertise from surgeons. Therefore, this study explored a safe and feasible surgical method for the complete resection of this type of tumor.MethodsWe collected the medical records of a 44-year-old female patient with space-occupying lesions near the thoracic vertebrae.ResultsThe transthoracic approach could effectively expose the relationship between the tumor and adjacent tissues, reduce the patient’s additional injury, completely remove the tumor tissue, and repair the diaphragm defect well. The amount of blood loss during the operation was approximately 600 ml. After the operation, there was a small amount of pleural effusion, the patient recovered well, and no other complications occurred. Through follow-up for 3 months after the surgery, the patient had no other complications and his physical condition had recovered.ConclusionsFor patients with transthoracic and abdominal schwannoma complicated by diaphragmatic invasion, performing tumor resection using the transabdominal approach may be difficult, but the transthoracic approach may be a safe and feasible surgical option.